Smart konsumtion - Arvidsson, Rebecka; Holst, Madeleine; Nyström, Erika (2008)
We are more aware than ever about our impact on the common environment and the world's population. Consumption awareness can be one way to take social and environmental responsibility. This study aims to examine young adults' (19-30 years) attitudes toward consumption awareness in Sweden. Consumption awareness is treated in this study as the consumption of environmental and fair-trade labeled products that have been certified of a third party. The study is limited to everyday commodities, which in this case is groceries, household consumables and clothing. To get an accurate understanding of young adult attitudes both qualitative and quantitative methods were used. The study is based on in-depth interviews with focus groups as well as a questionnaire survey. Initially, in-depth interviews were conducted to later be used as a basis for our focus group discussions. In order to reach a larger population, a questionnaire was used as a complement to the two previous methods. The combination of these three methods is referred to as triangulation and is used to give a broader and more accurate representation of the examined subject matter. Because of the relatively dynamic market developments and un-researched subject, the study is of an exploratory nature. The results can not be generalized; they only give a thorough representation of the participants' attitudes.